Penerapan Model Pembelajaran STAD (Student Teams Achievement Division) untuk Meningkatkan Hasil Belajar Materi Dimensi dan Struktur Pembelajaran IPS di Kelas V Sekolah Dasar Negeri 05 Sungai Pinang - Winingsi, Kartika Rama; Agustin, Lystiya; Nikmah, Nila Alfiatun; Patmawati, Patmawati; Puspitah, Yenda (ANTHOR: Education and Learning Journal, 2023)
The background of this research is that children do not like social studies lessons and children feelbored with the material. This research aims to improve social studies learning outcomes in dimensions and structure material through the application of the STAD (Student Teams Achievement Division) learning model for fifth-grade students at SD Negeri 05 Sungai betel nut. This research is a classroom action research (CAR) which is carried out in 2 cycles and 4 stages consisting of planning, implementing, observing, and reflecting. the subject of this study was the fifth children of SD Negeri 05 Sungai Pinang, data collection techniques used observation and assignments in the core activities, to obtain information about students' activeness in participating in the teaching and learning process and seeing social studies learning outcomes in material dimensions and structure. Social studies learning outcomes on dimensions and structure are said to have increased. It can be seen from the results of cycle II that there was an increase of 86, 66 %. This increase is due to changes in the use of learning models that are by the conditions of students so that students more easily understand the material and learn more actively in collaboration. As well as increasing the sense of responsibility in carrying out the task.